2007
DOI: 10.4028/www.scientific.net/ssp.124-126.1645
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Characteristics of Products Using Rotary Swaging Machine with Four-Dies

Abstract: Experiments under a cold rotary swaging process have been conducted to investigate the dimensional characteristics of the swaged tube and solid bar for obtaining proper product of desirable quality. Dimensional characteristics are expressed in terms of dimensional deviation and surface roughness of swaged product through the rotary swaging process. The process variables such as forming speed and percent reduction of outer diameter of the product are considered and selected because of playing a key role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Consequently, the impact pattern is further distorted. Despite this inhomogeneity and the discontinuous nature of the process, the combination of the axial feed per stroke value l st of the part and the circumferential shift of the dies between consecutive strokes allows for producing parts with constant external properties, like final diameter, length, roundness and surface roughness, over the entire formed length [6]. During the process, every spot of the finished part experiences about 100 effective strokes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the impact pattern is further distorted. Despite this inhomogeneity and the discontinuous nature of the process, the combination of the axial feed per stroke value l st of the part and the circumferential shift of the dies between consecutive strokes allows for producing parts with constant external properties, like final diameter, length, roundness and surface roughness, over the entire formed length [6]. During the process, every spot of the finished part experiences about 100 effective strokes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out to establish optimal process conditions concerning surface quality and geometry, e.g., by analyzing the influence of dry process conditions [5], feed per stroke values [6], radial feed per stroke values during plunge rotary swaging [7] or true strain [8]. Furthermore, the internal properties of the part, such as its microstructure, hardness and residual stress components, which are important for its strength, have been investigated: Lim found that the hardness at the outer surface increased with increasing diameter reduction of steel tubes [9] and Kocich stated that rotary swaging induces a strong fiber texture in tungsten heavy alloys [10].…”
Section: Introductionmentioning
confidence: 99%
“…But also process parameters influence the workpiece quality. The surface finish strongly depends on the feed rate of the workpiece [3], whereas the variation of the final diameter mainly depends on the overall deformation degree [4].…”
Section: Introductionmentioning
confidence: 99%
“…With the work hardening effect, the strength of the workpiece can be improved, which makes it possible to replace some expensive materials with cheaper materials [3,4]. Additionally, after the process, the surface condition could be improved with a lower roughness than the initial state [5]. Except for widely used structural steel and soft materials like aluminum, this process is able to deform metals like titanium, magnesium, and tungsten [6].…”
Section: Introductionmentioning
confidence: 99%